Regulating Social Life Discourses on the Youth and the Dispositif of Age - Ostrowicka, Helena (Postdisciplinary Studies in Discourse,, 2019)
This book presents the original concept of the 'dispositif of age', combining post-Foucauldian analytics of the dispositif, discourse and governmentality with the historical semantics of Reinhart Koselleck to explore the functions of the notion of youth in the regulation of social life. Making use of examples from sources including scientific and media statements, youth policy programmes, and strategies at international (European) and local (Polish) levels, the author shows how this concept of youth supports processes of social regulation and contributes to the implementation of political goals as specific responses to issues such as radicalization and violence, unemployment, and economic crisis. This book will be of interest not only to scholars of discourse and youth studies, but also to all post-Foucauldian researchers with an interest in going beyond simple 'applicationism'. Helena Ostrowicka is Associate Professor and Chair of Research Methodology and Discourse Studies at Casimirus the Great University in Bydgoszcz, Poland. She is interested in the issues of broadly understood educational, youth, and scientific policy. She focuses on exploring the post-Foucauldian perspective in the analysis of discourse, and the relations of knowledge and power in four institutional contexts: education, science, politics, and the media.